THE COMPARISON OF MAIN CHARACTER AND PLOT IN THE SNOW WHITE AND THE SEVEN DWARFS (1937) AND SNOW WHITE AND THE HUNTSMAN (2012) MOVIE (COMPARATIVE LITERATURE APPROACH) - Riskiandini, Novita; Susilowati , Endang (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2024)
This paper discusses two different Snow White movies, namely, Snow White and the Seven Dwarfs (1937) and Snow White and the Huntsman (2012). The title of this paper is The Comaprison Of Main Character And Plot In The Snow White And The Seven Dwarfs (1937) And Snow White And The Huntsman (2012) Movie (Comparative Literature Approach). The purpose of the study is to describe the similarities and differences in the storyline and the representation of the main characters in both movies. The method used is Descriptive Qualitative with a comparative literature theory approach. The results of the study show that in the animated movie, Snow White relies on the help of others in the story, while in the live action film, the character of Snow White is depicted as a strong woman and is able to change the story herself. Keywords: Snow White, Comparative, Movie